Exactitude : On Precision and Play in Contemporary Architecture - Davis, Michael Trabue; Katsaros, Laure; Riahi, Pari (Architect) (Book collections on Project MUSE., 2022)
"Precision is necessary in the field of architecture, and new technologies have increased demands for accuracy, particularly when the smallest errors can have outsized consequences. However, the importance of precision, or exactitude, has not received the consideration it merits. While themes of sustainability, performance, and formal innovation have been at the forefront of architectural scholarship for the past twenty years, this book moves beyond these concerns to explore the theoretical and practical demands exactitude makes on architecture as a field. The eleven essays collected here investigate the possibilities and shortcomings of exactitude and delve into current debates about the state of contemporary architecture as both a technological craft and artistic creation. Featuring new work by leading theorists, historians, editors, architects, and scholars, this volume brings theory and practice into insightful and productive conversations. In addition to the editors, contributors include Mark Wigley, Alejandro Zaera-Polo, Eric Höweler, Christopher Benfey, Sunil Bald, Ada Tolla and Giuseppe Lignano with Thomas de Monchaux, Alicia Imperiale, Francesca Hughes, Teresa Stoppani, and Cynthia Davidson"--